Ovarian follicular development, hormonal and metabolic profile in prepubertal ewe lambs with moderate dietary restriction and lipid supplementation - Junqueira, Felipe Barbosa; Souza, José Camisão de; Campos, João Pedro Araújo; Faria, Letícia Rodrigues; Silva, Débora Regina da; Ascari, Ivan Júnior; Lima, Renato Ribeiro de; Furusho-Garcia, Iraídes Ferreira; Nogueira, Guilherme de Paula [UNESP]; Alves, Nadja Gomes (Elsevier, 2019)
To evaluate the effects of moderate dietary restriction and lipid supplementation on ovarian follicular development, hormonal and metabolic profile, thirty-five prepuberal ewe lambs were blocked by body weight and randomly assigned to treatments: AL–US (control) - unsupplemented-diet ad libitum (3.5% ether extract, n = 9); R-US - intake restricted to 85% of the AL–US diet (n = 9); AL-LS - lipid-supplemented-diet ad libitum (9.8% ether extract, n = 8); R-LS - intake restricted to 85% of the AL–LS diet (n = 9), from 95 ± 8 days of age until estrus or 7 months of age. Lipid supplementation did not reduce dry matter intake. Daily weight gain was greater in lambs fed ad libitum. Plasma glucose was greater in the R–LS treatment group, while serum insulin was less with lipid supplementation. There was a treatment by age interaction on total cholesterol, HDL cholesterol and triglyceride serum concentrations. Estrus was detected in 43% of the animals and the overall ovulation rate was 60%. The number of follicles, diameter of the largest follicle, body weight, age and serum progesterone at puberty did not differ among treatment groups. The mean diameter of the largest follicle was greater in lambs having than in those not having ovulations and increased with age in both groups. There was an interaction between the effects of occurrence of ovulation and age on the number of follicles between 3 and 5 mm and > 5 mm. Lipid supplementation and dietary restriction altered the metabolic profile in ewe lambs with no concomitant changes in values for reproductive variables.
Keywords: Cholesterol; Insulin; Ovulation; Progesterone; Roasted soybean